Case report: Equine metacarpophalangeal joint partial and full thickness defects treated with allogenic equine synovial membrane mesenchymal stem/stromal cell combined with umbilical cord mesenchymal stem/stromal cell conditioned medium - Reis, I. L.; Lopes, B.; Sousa, P.; Sousa, A. C.; Rêma, A.; Caseiro, A. R.; Briote, I.; Rocha, A. M.; Pereira, J. P.; Mendonça, C. M.; Santos, J. M.; Lamas, L.; et al. (Frontiers in Veterinary Science, 2024)
Here we describe a case of a 5-year-old show-jumping stallion, presented with severe lameness, swelling and pain on palpation of the left metacarpophalangeal joint (MCj). Diagnostic imaging revealed full and partial-thickness articular defects over the lateral condyle of the third metacarpus (MC3) and on the dorsolateral aspect of the first phalanx (P1). After lesion's arthroscopic curettage, the patient was subjected to an innovative regenerative treatment consisting of two intra-articular injections of equine synovial membrane mesenchymal stem/stromal cells (eSM-MSCs) combined with umbilical cord mesenchymal stem/stromal cells conditioned medium (UC-MSC CM), fifteen days apart. A twelve-week rehabilitation program was accomplished and lameness, pain and joint effusion remarkably reduced however magnetic resonance imaging (MRI) and computed tomography (CT) scan presented incomplete healing of the MC3's lesion, prompting a second round of treatments. Subsequently, the horse achieved clinical soundness, returned to a higher level of athletic performance and imaging exams revealed absence of lesions at P1, fulfilment of the osteochondral lesion and cartilage-like tissue formation at MC3's lesion site. The positive outcomes suggest the effectiveness of this combination for treating full and partial cartilage defects in horses. Multipotent mesenchymal stem/stromal cells (MSCs) and their bioactive factors compose a novel therapeutic approach for tissue regeneration and organ function restoration with anti-inflammatory and pro-regenerative impact through paracrine mechanisms.